Molecular validation for blast and sheath blight resistance in improved rice genotypes and landraces - P. SHARMA, A. KUMAR, A.K. SINGH, S. GOPALAKRISHNAN, R. RATHOUR; U.D. SINGH*, A.K. DUBEY, R.T.P. PANDIAN, H. RAJASHEKARA, A. KHANNA, R.K. ELLUR (Indian Phytopathology, 2014)
Globally, two major fungal diseases viz., blast caused by Magnaporthe oryzae and sheath blight incited by Rhizoctonia solani Kuhn. of rice occur in most of the rice-ecosystems resulting in significant yield losses. Host plant resistance is the most eco-friendly management option for combating biotic stresses. In the present study, a set of one hundred rice genotypes were evaluated for blast as well as sheath blight resistance. Twenty seven genotypes were identified to be resistant against M. oryzae isolate (Mo-ni-0066). These genotypes were subjected to molecular validation using the markers linked to major R-genes, viz., Piz5, Pi9, Pita, Pi54, Pi1 and Pib. Individually none of the entries could be observed to possess all these R-genes. However, some of the resistant genotypes were found to possess one or more R-genes. But, evaluation of these genotypes with highly virulent M. oryzae Karnataka isolate (Mo-si-mnd) revealed that only two genotypes viz., Bhusan San and P1490-03 were resistant to blast. Interestingly, molecular validation of these two genotypes did not show any of the above resistance genes, indicating the possible role of some other R-gene/s. When the same set of one hundred rice genotypes were screened for sheath blight resistance, none of the rice genotypes were resistant. However, four genotypes were observed to possess high degree of tolerance to sheath blight and were assessed for the major sheath blight quantitative trait loci qSBR11-1.